2021
DOI: 10.1155/2021/6630043
|View full text |Cite
|
Sign up to set email alerts
|

An Adrift and Homeless Cyst within the Peritoneal Cavity

Abstract: Introduction. Echinococcosis is a zoonotic infection caused by Echinococcus species. Iran is endemic for Echinococcus granulosus. Here, we present a case of hydatidosis in an 85-year-old man, presented with acute, dull, constant, and generalized abdominal pain. A computed tomography scan (CT scan) showed an intact hydatid cyst on the bladder dome and several hydatid cysts in the liver. Open surgery revealed a cyst with hepatic origin, confirmed with histopathological studies. Conclusion. Although a primary abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Regarding the abdominal cavity, the retroperitoneum in back and forth and the peritoneum in the middle are among the rarest sites, as a study reported that peritoneal and pelvic cavity hydatid cysts account for only about 2%–5% of the total cases diagnosed with CE 12 . As several studies reported, the CE in these sites is mainly presented with abdominal pain due to the mass effect caused by hydatid cysts 4,9,12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the abdominal cavity, the retroperitoneum in back and forth and the peritoneum in the middle are among the rarest sites, as a study reported that peritoneal and pelvic cavity hydatid cysts account for only about 2%–5% of the total cases diagnosed with CE 12 . As several studies reported, the CE in these sites is mainly presented with abdominal pain due to the mass effect caused by hydatid cysts 4,9,12 …”
Section: Discussionmentioning
confidence: 99%
“…12 As several studies reported, the CE in these sites is mainly presented with abdominal pain due to the mass effect caused by hydatid cysts. 4,9,12 Previous studies have indicated that hydatid cysts can also be found in the abdominal wall (Table 1). According to a review by Salih et al, primary hydatid cysts in the abdominal wall are a rare disease with only six reported cases up to date.…”
Section: F I G U R Ementioning
confidence: 99%
See 2 more Smart Citations